DEVELOPMENT OF 3D AUGMANTED REALITY TEACHING MATERIALS BASED ON VIRTUAL TECHNOLOGY AS LEARNING MEDIA - Fattachul Huda Aminuddin; Teuku Djauhari (Dinasti Publisher, 2021)
Augmented Reality is a concept that combines virtual reality with world and a way to explore 3D objects. This game-based learning application has advantages in terms of more interactive and effective use, and is complemented by simple object modelling that can be widely applied in various media and is very supportive of interface technology through smartphone applications. The purpose of this research is to produce a learning media product by utilizing the development of Augmanted Reality- based 3D Virtual Technology using the marker and Unity 3D platforms in high school ICT Subjects in learning in the era of the industrial revolution 4.0 which is valid, practical and effective to foster critical thinking skills, improving and developing life skills that are realized through the achievement of student competencies. The type of research used is development research with a 4D (Four-D) model approach including the stages of define, design, develop and disseminate. Based on the results of the validation test research, the results obtained from the Content aspect of the media were 0.835 with the Valid category, from the media experts assessed from the media format aspect of 0.84 in the Valid category, and the media presentation aspect obtained Aiken's V value of 0.845 with the Valid category. The practicality of Augmanted Reality-based 3D Virtual Media was obtained from the teacher's response and student responses, from the teacher's response it was obtained an average of 88.57% with the very practical category and the student response was 81.63% with a very practical level of practicality. The effectiveness of 3D virtual media based on Augmanted Reality is obtained from the students' learning scores after using the media with the number of students who passed is 17 students (85%) out of 20 students and stated that the media is effective to improve student learning outcomes through the Gain score test with a value of 0.53 with category moderate. It is hoped that this application and can be developed again by researchers so that this application can help and support teachers in supporting the success of the student learning process.